DIGITAL LEADERSHIP DALAM MANAJEMEN PENDIDIKAN: PENDEKATAN STRATEGIS UNTUK MEWUJUDKAN TATA KELOLA PENDIDIKAN YANG ADAPTIF, INOVATIF, DAN BERKELANJUTAN - Ahyar; Azhar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital leadership is a key approach in the transformation of educational management in the digital age. This study aims to synthesize various findings regarding the characteristics, implementation, challenges, and contributions of digital leadership in educational management. The study employs a literature review using a descriptive qualitative approach, analyzing 13 scholarly articles published between 2021 and 2026 that were obtained through Google Scholar. The results of the study indicate that digital leadership integrates strategic vision, technology, innovation, and data-driven decision-making. Its implementation enhances the effectiveness of educational governance through the strengthening of organizational culture, the development of human resource competencies, and the optimization of educational services. However, its implementation still faces obstacles in the form of infrastructure limitations, low digital literacy, resistance to change, and suboptimal policy support. These findings underscore that digital leadership serves as the foundation for achieving adaptive, innovative, and sustainable educational governance, with the success of digital transformation determined by leadership capacity in managing organizational change.